Chinese police and its support for the use of force - Liu, Shelley (Journal of ethnicity in criminal justice, 2023)
This study examines patterns and determinants of police attitudes toward the use of force in China. Using police use of force scenarios to elicit officers’ opinions about force used by other officers, this study finds that the way officers view police use of force vary significantly by officers’ age, education, and police division to which an officer is assigned. Regression analysis demonstrates that officers’ adherence to traditional police subcultural themes—code of silence and aggressive approach to policing—are prominent predictors of attitudes supportive of the use of force. The positive association between educational attainment and police attitudes toward the use of force is discussed in relation to China’s socio-political environment. Policy implications for police recruitment, training, and management are discussed as well.